(untitled) (Andamios, Revista de Investigación Social, 2007)
Using Michel Foucault’s genealogical method, this paper argues that human rights consciousness first appeared in Mexico as the result of an eclectic combination of two political tendencies: transition to democracy and liberation theology. In this way of thinking, civil and political rights were considered to have the same importance as economic, social, and cultural rights. However, human rights cause lost ground as it became subordinated to the transition-to- democracy cause, and human rights issues related to socio-economic inequality were put on the back burner. As the economic situation worsened, NGOs are finally addressing economic and social problems, but have not been able to revert the effects of years of neglect.